ZAPS Zu- und Angehörige Pflege Spiritualität: Family Caregivers and Spirituality (DRKS00036594) : Development and evaluation of an intervention for family caregivers - Kubitza, Jenny; Haußmann, Annette; Frick, Eckhard (Spiritual care, 2025)
Family caregivers (FCs) suffer from multiple strains, which have a negative impact on their health and well-being. Spirituality can be a resource to mitigate the FCs’ burdens. The study aims to develop and evaluate a spiritual intervention for FCs. The evaluation will be conducted as a mixed methods study: a) the qualitative approach examines the FCs’ experiences with the intervention, and b) the quantitative randomised controlled intervention study examines the effect of the intervention on the FCs’ spiritual well-being, life satisfaction, and subjective distress. In the quantitative survey, 194 FCs will be surveyed and 20 FCs in the qualitative part. The data will be collected at various times and analysed qualitatively using the content analysis according to Mayring and quantitatively using statistical methods. The study will presumably start in May 2025 and continue until March 2027.